2013
DOI: 10.1021/jm3016987
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Non-natural Amino Acids Improves Cell Permeability and Potency of Specific Inhibitors of Proteasome Trypsin-like Sites

Abstract: Proteasomes degrade the majority of proteins in mammalian cells by a concerted action of three distinct pairs of active sites. The chymotrypsin-like sites are targets of antimyeloma agents bortezomib and carfilzomib. Inhibitors of the trypsin-like site sensitize multiple myeloma cells to these agents. Here we describe systematic effort to develop inhibitors with improved potency and cell permeability, yielding azido-Phe-Leu-Leu-4-aminomethyl-Phe-methyl vinyl sulfone (4a, LU-102), and a fluorescent activity-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
108
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(115 citation statements)
references
References 41 publications
6
108
1
Order By: Relevance
“…20 We hypothesized that additional inhibition of β2 proteasome activity in bortezomib-resistant myeloma cells would increase the degree of proteasome inhibition achieved by bortezomib alone, and re-sensitize them for bortezomib treatment via IRE-1a activation and induction of a terminal UPR. With this aim in view, we have developed the first synthetic proteasome inhibitor to inhibit the β2 activity, 21 and have improved its cell permeability and potency, yielding the compound LU-102, 22 which sensitizes RPMI8226 cells to bortezomib and carfilzomib-induced cytotoxicity. We now address the potential of LU-102 to overcome bortezomib/carfilzomib-resistance.…”
Section: Correspondence: Christophdriessen@kssgchmentioning
confidence: 99%
See 1 more Smart Citation
“…20 We hypothesized that additional inhibition of β2 proteasome activity in bortezomib-resistant myeloma cells would increase the degree of proteasome inhibition achieved by bortezomib alone, and re-sensitize them for bortezomib treatment via IRE-1a activation and induction of a terminal UPR. With this aim in view, we have developed the first synthetic proteasome inhibitor to inhibit the β2 activity, 21 and have improved its cell permeability and potency, yielding the compound LU-102, 22 which sensitizes RPMI8226 cells to bortezomib and carfilzomib-induced cytotoxicity. We now address the potential of LU-102 to overcome bortezomib/carfilzomib-resistance.…”
Section: Correspondence: Christophdriessen@kssgchmentioning
confidence: 99%
“…AMO-abtz/acfz cells were adapted to proteasome inhibitor-containing culture conditions as described. 20 The proteasome inhibitors bortezomib, carfilzomib and LU-102 22 were synthesized at the Leiden Institute of Chemistry. The selective inhibitors NC-001 (inhibiting β1/β1i) and NC-005 (β5/β5i) have been described by Britton et al…”
Section: Cells and Inhibitorsmentioning
confidence: 99%
“…The RLR recognition element was more active against purified proteasomes, but less active in cells, presumably due to poor cell permeability. Geurink et al subsequently reported that vinyl sulfones are more potent and selective toward the b2 subunits than their epoxyketone analogs [43]. Furthermore, replacement of arginine with the non-natural amino acid 4-(aminomethyl) phenylalanine in either the P1 site (LU012) [43] or P1 and P3 sites (LU112) further improved affinity and chemical stability.…”
Section: Subunit-selective Abpsmentioning
confidence: 99%
“…These compounds have an azide handle that can be used for attachment of biotin or a fluorophore after labeling. However, introduction of the fluorophore prior to labeling reduced selectivity over the b5 subunit [43]. Despite the trypsin-like selectivity of b5, a basic residue in the P1 site is not required.…”
Section: Subunit-selective Abpsmentioning
confidence: 99%
See 1 more Smart Citation